NGHIÊN CỨU CHẾ TẠO HỘP XÚC TÁC XỬ LÍ KHÍ THẢI ĐỘNG CƠ BẰNG KIM LOẠI MẠ NIKEN COMPOSIT NANO CESI ĐIÔXÍT - Hùng, Nguyễn Đức; Dư, Đào Khánh (Vietnam Journal of Science and Technology, 2012)
SUMMARY RESEARCH ON MANUFACTURING OF CATALYTIC BOXES FOR ENGINE EXHAUST TREATMENT BY COATING OF NICKEL NANOCOMPOSITES WITH CERIUM DIOXIDE Catalytic exhaust treatment has been studied by making CeO2 coated steel sheets. The catalytic surface area reached 2.32 m2 and the volume space to achieve exhaust emission levels of 0.638 cm3 and the amount on-surface catalyst was determined to be of 3.39 ÷ 6.74%, which all are equivalent to those parameters of imported ceramic form. With the made device the optimal position to localize the catalytic box was found, for which the system was capable of handling gas HC emissions of 29.1 % as measured by oxygen sensor. With the engine operating regime without sensor, the amount of treated HC and CO were 41% and  67%, respectively. The  performance of exhaust gases treatment by use of the CeO2 catalytic coated steel sheets exhibited to improve significantly for the working temperature of 400 oC which was gained when the engine operating at high speed mode. Keyword. Catalytic box, engine exhaust treatment, nanocomposit coating, cerium dioxide.